Reference Architectures for Self-Managed Software Systems: A Systematic Literature Review - Affonso, Frank J.; Scannavino, Katia R. F.; Oliveira, Lucas B. R.; Nakagawa, Elisa Y. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2014: Anais do VIII Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2014)
Self-Managed Software Systems (SMSS) have emerged as an important type of software systems. However, the development of such systems is not a trivial task, as they constantly deal with adaptations at runtime so as to fulfill new needs of both users and execution environment. From another perspective, Reference Architectures (RAs) have been used for the aggregation of knowledge on specific domains, promoting the reuse of design expertise and facilitating the development, standardization, and evolution of software systems. Considering the relevance of such architectures, RAs for SMSS (RA4SMSS) have also been proposed. On the other hand, to the best of our knowledge, no study on a panorama or comparison on RA4SMSS has been published. This paper reports the results of a systematic literature review on RA4SMSS. They show that although relevant initiatives have been found, the SMSS area needs a broader contribution to boost the development of such systems. Moreover, research lines that must further investigated were also identified.